Training medical students in global health education through framework of entrustable professional activities - Saurabh RamBihariLal Shrivastava; Shubhada Gade; Alka Rawekar (Journal of Education and Health Promotion)
Global health education aims to improve health standards and achieve health equity by reducing health disparities across national boundaries. In the context of global health education, entrustable professional activities (EPAs) provide a clear framework for defining specific, observable activities that a student must be able to perform independently, without supervision. To equip medical students with global health-related competencies, framing EPAs becomes crucial. This task begins with identifying the core competencies essential for effective global health practice. In conclusion, EPAs are expected to play a defining role in global health education. The need of the hour is to engage all stakeholders, systematically select the EPAs that are crucial for delivering global health education, and train medical students in the desired competencies to empower them to deliver effective healthcare services.